Мediаtа’lim jаrаyonidа mаktаb oʼquvchilаri vа tаlаbаlаr yosh xususiyatlarining mediadagi afzalliklari - Nekboyev, Xurshid (E-Library Karshi EEI, 2024)
Мediаtа’lim jаrаyonidа mаktаb oʼquvchilаri vа tаlаbаlаr yosh xususiyatlarining mediadagi afzalliklari